The Public Sector Accounting Reform of 2014 in the Light the Experiences of the Local Governments: A Pilot Project to Explore the Problems - Tóth, Balázs (Public Finance Quarterly, 2020)
The renewal of public finance accounting in 2014 can be labelled as one of the greatest changes in the Hungarian public sector. The accounting information system used previously had significant shortcomings, which ultimately led to disruptions in the operation of the local government system and its indebtedness. The aim of the research is to explore the experience of the local governments regarding the process of the introduction of the accounting reform and the emerging system. In the research, interviews and small group sessions were conducted with 18 experts from 8 institutions. Based on what was said, the transitional period was a turbulent process, and compliance with the new regulation tested the adaptability of local governments. The opinions regarding the new system are heterogeneous. According to the involved experts, the new approach can provide a more true and fair view and present up-to-date information about the given organisational unit. However, the introduction of the new system was not fully successful as the new system proved to be more complex and more difficult to handle. In addition, it was also revealed that in most cases the data of the accounting information system fail to fulfil their intended purpose in financial management.